Prevalence of Insomnia among Emergency Doctors and their Physiological Link with Serum Melatonin: Key to Better Sleep among Doctors of LUMHS - Jehanzeb Jahangir Dars, Salma Farukh Memon, Arsalan Ahmed Uqaili, Shakeel Shaikh, Moomal Tagar, Sana Jawad (Pakistan Journal of Medical & Health Sciences, 2022)
Background: As a consequence of the epidemic, health care workers have been subjected to unusual levels of stress, anxiety, and sleep issues. Chronic insomnia is usually linked to circadian rhythm abnormalities. Insomnia is a frequent indication of a lack of serum melatonin. Objective: To detect the prevalence of Insomnia among doctors at LUMHS and their physiological role with regard to serum melatonin levels. Methodology: This cross-sectional study was conducted involving 116 doctors, out of which male 48(41.3%) and female 68 (58.6%), working in all clinical wards of Liaquat University of Medical & Health Sciences, Jamshoro / Hyderabad from August 2021 to February 2022. Each patient’s demographic information was collected. Serum Melatonin levels in the blood were measured using an ELISA KIT. Along with (Insomnia severity index) questioner was filled out by each participant. SPSS version 26 was used to analyze the collected data. Results: This study found that physicians’ sleep and wake cycles are disrupted owing to their long, stressful working hours, out of 116 participants, 42.68 percent experienced insomnia. Regardless of age, gender, or BMI, Insomnia was shown to be co- related with a lower blood melatonin level (r value=-.585**, p=0.001). Conclusion: The findings of this investigation are in line with our hypothesis that reduced serum Melatonin levels in insomniacs lead to delayed signal transduction, causing circadian oscillator system anomalies. We have found that insomnia among doctors shows significant variations in relation to department, sex, designation, and working hours. Further addressing it requires molecular studies. Keywords: Insomnia, Prevalence, Serum Melatonin, sleep disturbance